Skyrmionium – high velocity without the skyrmion Hall effect. Issue 1 (December 2018) - Kolesnikov, Alexander; Stebliy, Maksim; Samardak, Alexander; Ognev, Alexey
Abstract The lateral motion of a magnetic skyrmion, arising because of the skyrmion Hall effect, imposes a number of restrictions on the use of this spin state in the racetrack memory. A skyrmionium is a more promising spin texture for memory applications, since it has zero total topological charge and propagates strictly along a nanotrack. Here, the stability of the skyrmionium, as well as the dependence of its size on the magnetic parameters, such as the Dzyaloshinskii–Moriya interaction and perpendicular magnetic anisotropy, are studied by means of micromagnetic simulations. We propose an advanced method for the skyrmionium nucleation due to a local enhancement of the spin Hall effect. The stability of the skyrmionium being in motion under the action of the spin polarized current is analyzed.